Trust in Governmental Health Communication on Covid-19 - David Schieferdecker; Philippe Joly; Natalie Berger (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
Trust in governmental communication is critical to the successful containment of public health crises. However, in highly politicised crises, trust varies as a function of partisanship. This research report examines the relationship between political preferences and trust in governmental health communication during the Covid-19 pandemic in Germany. We pay particular attention to the interaction between (a) different dimensions of vulnerability to the virus and (b) distrust rooted in partisan preferences. Using original data from a representative, four-wave online survey conducted in Germany in 2020 and 2021, we found moderate to low levels of trust in information from the government. Whereas belonging to a vulnerable age group (65+) and fear of infection were significantly associated with trust, identification as a member of a risk group was not. Voters of the right-wing populist AfD were less likely to trust government information. Finally, the association between fear of infection and trust was stronger among AfD voters than among voters of established parties. We conclude that public health campaigns should account for the fact that politicised individuals may not trust communicators in prolonged crises. Messages targeting members of risk groups and partisans of populist parties should make health risks relatable to them as individuals.